The Development of Da'wah Through Tabligh and the Development of Da'wah Ideas in Indonesia - Gantira, Erlan (STAI AL-FALAH CICALENGKA, 2023)
Now, tabligh preaching through oral and written lectures can be combined into one medium, namely digital media, so the preachers' abilities must be even more capable because media can now become a convergent media, namely a combination of written and video/film media. The condition of tabligh preaching in the midst of increasing political behavior brings challenges and notes for preachers to choose neutral ideas or lecture material, because basically Islam is a religion of Rahmatan lil allamin, always providing peace and tranquility for all creatures and their lives. Da'wah ideas and materials do not have to be titles and preaching materials but also other ideas that are easily accepted in society, enter into their social behavior and social strata, so that they become an